Escolas de governo e a profissionalização do servidor público: estudo de caso da ESPEA - Escola de Serviço Público do Estado do Amazonas e da FESPM - Fundação Escola de Serviço Público, Municipal, da prefeitura de Manaus - Bittencourt, Maryângela Aguiar (2008)
School of Government and Professional Server is the subject of this thesis aimed at analyzing the mission of each and its contribution to the training of all operators in the state administrative structure. The experiences in the field of management training, capacity building and training of civil servants in public administration from national and international experiences, allow the establishment of information concerning the professional profiles required for the Brazilian public administration in the current context and the appropriate institutions for the production these profiles. To this end, reconstructs the institutional history of ENAP - National School of Public Administration / Brazil and brings slopes analysis to be tested in other schools. In order to promote debate the Latin American context is widespread, as the attempt to periodization and analysis of 80 years raising a general review of common features that point to help contextualize and expand the debate that rages in each country about the prospects these government schools. In the 80's is emphatically defended the existence and definition of an ideal profile of professional public administration, today, the discourse has changed since 90 years, the rapid degree of change and complexity installed within organizations by technological advance and the rearrangement of the economic and cultural boundaries derived from globalization have highlighted the need for treatment and more careful scrutiny to the issue, requiring additional effort to escape from solutions in mixtures of a profoundly heterogeneous. Thus, it takes as a case study the experiences of ESPE and FESPM both located in the city of Manaus in Amazonas state for review of the purpose of each of the schools, where they helped train new cadres of public servants and also, prepared new leadership for the development and improvement of the state machine. The methodological guidelines used were based on two criteria Vergara (2006), about the purposes and the means with basic technical and empirical-analytic approach, the means of investigation was the documentary, literature and exploratory (field research, through interviews with former teachers and former students of schools). The results of the collective responses of the subjects were consolidated into a single speech when the same opinion emphasizing the central idea of each of the speeches delivered and how many people the same idea. It was concluded that the government schools can contribute to the professionalization of public servants and recommended development of programs for schools that will graduate in public administration, developing skills for the public servant and advice to create plans for capacity building of bodies’ government playing a significant role in personal and professional public servant.